Tackling inequality is essential for behaviour change for net zero - Kukowski, CA; Garnett, EE (Springer Nature, 2023)
Policies and psychological approaches often overemphasize individual agency, overlooking how socioeconomic inequality can constrain access to low-carbon alternatives. We argue that tackling these inequalities is urgent for impactful, equitable behaviour change.